Sociodrama com adolescentes: revelações para o cuidar em saúde - Yadja do Nascimento Gonçalves; Annatália Meneses de Amorim Gomes (Revista Brasileira de Psicodrama, 2020)
Adolescence is a stage of social development, the phase of identity development and affirmation of the individual’s autonomy, these conditions being vital for the practice of citizenship, multiple rights Yadja do Nascimento Gonçalves Psicóloga e Assistente Social. Professora Doutora do Programa de Pós-Graduação em Saúde da Criança e do Adolescente da Universidade Estadual do Ceará (UECE). Annatália Meneses de Amorim Gomes 42 and health  care. Using a sociodramatic frame of reference, this study aims to understand the perceptions of adolescents of their experienceof adolescence. It is therefore a qualitative intervention in the area of health with adolescent patients of a pediatric outpatient unit in a public hospital. This sociometric proposal offers reflection on the professional practice from an integrative perspective of adolescence within the public health. It emphasizes the importance of this method in hospital settings as a facilitator of individuals’ free expression, and the redemption of autonomy and agency in self care. do protagonismo no cuidado de si.